2012
DOI: 10.1007/bf03261929
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Clearance and Volume of Distribution in the Obese from Normal Weight Subjects

Abstract: The study indicated that allometric scaling can be applied to predict CL in the obese from normal weight subjects with high accuracy. The predicted CL can then be used to select a dose to initiate a clinical trial (pharmacokinetics, safety and efficacy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Nevertheless, nonlinear functions of total body weight (TBW) show good performance as predictors of clearance in several pharmacokinetic studies covering wide ranges in body weight (74,75,78). Similarly, in a large study on the variation in clearance and volume of distribution of 12 different drugs, total body weight appeared to be a consistent and reliable size descriptor for the prediction of these parameters in the obese (79).…”
Section: Measures To Quantify Body Size and Overweightmentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, nonlinear functions of total body weight (TBW) show good performance as predictors of clearance in several pharmacokinetic studies covering wide ranges in body weight (74,75,78). Similarly, in a large study on the variation in clearance and volume of distribution of 12 different drugs, total body weight appeared to be a consistent and reliable size descriptor for the prediction of these parameters in the obese (79).…”
Section: Measures To Quantify Body Size and Overweightmentioning
confidence: 94%
“…In obese subjects, changes in volume of distribution may be expected to result from increased blood volume, increased cardiac output and blood flow, increased LBW, increased adipose tissue and reduced tissue perfusion (19-22, 91, 92), with only a limited influence of changes in blood proteins (i.e., albumin, alpha acid glycoprotein) (23,94). From the available evidence, the values of the volume of distribution appear highly variable in obese individuals and more difficult to predict than the values of clearance (79,90). While intuitively more influence of obesity on lipophilic drugs than on hydrophilic drugs may be expected (93), Jain et al (90) concluded, on the basis of an overview of the ratios of volume of distribution of various drugs in obese versus nonobese individuals, that changes in volume of distribution cannot be predicted on the basis of lipophilicity alone.…”
Section: The Influence Of Obesity On Drug Distributionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the human clearance of SMs is more predictable combining in vitro and in vivo animal data by means of well-stirred model and commonly used allometric scaling etc [95][96][97][98][99]. The examples applying allometric scaling have been reviewed for predictions of clearance and volume distribution of therapeutic proteins recently [37].…”
Section: Analysis and Interpretation Of Preclinical Animal Pk Of Adcsmentioning
confidence: 99%
“…Investigators who focus only on obese subjects rather than a broad weight range that included normal-weight subjects, may not find a realistic allometric relationship [58]. Strange reports of negative exponents that imply clearance decreases with weight have been published [61].…”
Section: Propofolmentioning
confidence: 99%